KONDISI SOSIAL EKONOMI DAN PEMBERDAYAAN NELAYAN TANGKAP KOTA TEGAL, JAWA TENGAH - Deshinta Vibriyanti (Jurnal Kependudukan Indonesia, 2014)
Tegal city has the potential of fishing on fisheries, human resources and adequate infrastructure. However, the data indicate that fisheries production in Tegal experience fluctuated in the last five years due to tough weather and the occurrence of overfishing in the north of the Java fishing area. This condition affects fishing income is uncertain,especially for traditional fishermen who have limited capital and technology. Therefore it takes the government intervention in promoting the empowerment of fishermen through various programs. This study aimed to describe the socioeconomic conditions and the empowerment programs for the fishermen, particularly the traditional fishermen in Tegal. Data collected through qualitative approach in interviewing technique, Focus GroupDiscussions (FGD), observation and study of literature. The results of this study indicate that the fisheries sector in Tegal has great potential as a driver of the economy of local communities. This is evident from the growth of industries such as industrial fish processing fillet absorb labors, especially women workers. However, the empowerment program as provided by the government still having some problems in the field, especially in terms of equitable access to the program either physical or non-physical dimension. Grouping approach is one strategy to increase the participationof fishermen in the empowerment program. Therefore, the government needs to encourage fishermen to united into the groups to facilitate mapping and intervention programs. Assistance to fishing groups are also necessary, particularly for traditionalfishermen who in lower levels of education.Tegal city has the potential of fishing on fisheries,human resources and adequate infrastructure.However, the data indicate that fisheries productionin Tegal experience fluctuated in the last five yearsdue to tough weather and the occurrence ofoverfishing in the north of the Java fishing area. Thiscondition affects fishing income is uncertain,especially for traditional fishermen who have limitedcapital and technology. Therefore it takes thegovernment intervention in promoting theempowerment of fishermen through variousprograms. This study aimed to describe the socioeconomicconditions and the empowerment programsfor the fishermen, particularly the traditionalfishermen in Tegal. Data collected through qualitativeapproach in interviewing technique, Focus GroupDiscussions (FGD), observation and study ofliterature. The results of this study indicate that thefisheries sector in Tegal has great potential as adriver of the economy of local communities. This isevident from the growth of industries such asindustrial fish processing fillet absorb labors,especially women workers. However, theempowerment program as provided by thegovernment still having some problems in the field,especially in terms of equitable access to the programeither physical or non-physical dimension. Groupingapproach is one strategy to increase the participationof fishermen in the empowerment program. Therefore,the government needs to encourage fishermen tounited into the groups to facilitate mapping andintervention programs. Assistance to fishing groupsare also necessary, particularly for traditionalfishermen who in lower levels of education.